The Hitchhiker's Guide to Writing Research A Festschrift for Steve Graham - Liu, Xinghua; Hebert, Michael; Alves, Rui A. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book brings together the work of established scholars from around the world to celebrate and honor the many ways in which Steve Graham has contributed to the advancement of teaching and researching writing. Focusing on writing development and writing instruction in different contexts of education, original contributions in this book critically engage with theoretical and empirical issues raised in Steve Graham's influential body of work and significantly extend our understandings of the importance of writing in developing learners' literacy and the roles of writing in teaching and learning processes. This book is organized around themes central to Steve Graham's work, including theories and models of writing, effective instructional methods in teaching writing, surveys on teaching and learning writing, and systematic review studies on writing. Apart from regular chapters, the book also features personal and scholarly reflections revealing the powerful ways in which Steve Graham's work has influenced our thinking in the field of writing research and continues to open up new avenues for future research endeavors. .
Preface -- Part I: Theorizing Writing and Writing Research -- Self-Regulated Strategy Development: Evolution of an Evidence-based Instructional Model for Complex Learning and Emergent Areas of Research; Karen Harris -- A Model to Account for How Writers Choose Words to Express Their Emotions in Written Text; John Hayes -- Underlying Motivation of Writer(s) Within Community Model of Writing: More than Just Cherry Pie; Angelique Aitken -- A Meta Look at Writing Meta-Analyses: Where We've Come, Where We Are Now, and Where We Might Go Next; Tanya Santangelo and Michael Hebert -- Part II: Professional Development and Educational Reforms -- Professional Development Study on Self-regulated Strategy Development; Debra McKeown -- Teaching Chinese Characters in Primary Grades in Macao; Tien Ping Hsiang -- Teachers' Subject-Matter Content Knowledge and Pedagogical Content Knowledge; Gary A. Troia -- Postsecondary Developmental Education in Writing: Issues and Research; Charles A. MacArthur -- Part III: Teaching Writing Skills -- On Spelling Impact on Composing? A Longitudinal Study in Written French; Bernard Slusarczyk, Pascal Bressoux and Michel Fayol -- Is First Grade Children's Use of Academic Words in Writing Associated with Learning Science Topics? Jill Fitzgerald, Jackie Eunjung Relyea, Jeff Elmore and James Kim -- It was a dark and stormy sentence: Teaching the Fine Art of Sentence Construction; Bruce Saddler -- Influence of Linguistic Perspective on Expressive Writing; Rui A. Alves, Francisca Costa, Teresa Jacques and Ana Paula Azzam -- Supporting Writing and Writing Engagement through Promoting Regulation, Motivation and Perezhivanie; Clarence Ng and Peter Renshaw -- Part IV: Learner's Knowledge about Writing -- Changes in Writing Knowledge After Participation in an Integrated STEM and Writing-to-Learn Unit; Gillespie Rouse -- Elementary English Learner's Knowledge About Writing; Kay Wijekumar -- Facticity in Writing: Methods, Data, Evidence in Knowledge Production; Charles Bazerman -- What Makes Good Writing: Chinese EFL Learners' Perceptions and Practices; Xinghua Liu and Clare Furneaux -- Part V: Teaching Writing for Students at Risk -- Building Skills for Efficient Writing; Linda H. Mason -- Strategy Instruction for Secondary Students with Learning Disabilities and Struggling Writers: A Review of Empirical Research; Amber B. Ray -- Writing-to-Learn Mathematics Using SRSD for 5th and 6th Grade Special Education Students; Kiuhara, S. A., Levin, J. R., Tolbert, M.,Erickson, M. and Kruse, K. -- The Role of Executive Functions in Handwriting Performance of Higher-Education Students; Naomi Weintraub.
Keywords: Literacy; Educational psychology; Language and languages -- Study and teaching; Literacy; Educational Psychology; Language Education